Pengujian Antarmuka, Beban dan Kinerja, serta Keamanan Aplikasi pada Platform Belajar Online Myskill - Churun Ain Azkal Azkiya; Putri Dwi Mita Sari; Nufan Balafif (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Information system testing is a crucial step in software development. With the increasing number of users and the complexity of features on the MySkill platform, testing the information system is very important to ensure quality and usability. This research focuses on interface testing, load and performance testing, and vulnerability testing with a qualitative approach. The flow of research methods is preliminary studies, scenario design, installation, testing, data analysis and conclusions. Interface testing with Selenium IDE tools showed positive results, but there were problems with the bootcamp registration process. Load and performance testing using Apache Jmeter shows that MySkill has a consistent response time, with an average response time of about 2 seconds and a standard deviation of about 1.5 seconds. Vulnerability testing using OWASP ZAP shows that MySkill has 15 alerts with categories of high, medium, low and informative.